متلازمة تسرّع التنفس العابر عند الوليد وعوامل الخطورة - جوني, عدي; زاهر, محمد; عرداتي, مصطفى (Latakia University Journal -Medical Sciences Series, 2019)
تعدّ متلازمة تسرّع التنفس العابر عند الوليد حالة مرضية شائعة في جميع أنحاء العالم، مما يبرر الاهتمام المتزايد بتحديد عوامل الخطورة المختلفة لهذه المتلازمة. تناولت دراستنا83) وليداً) قُبلوا في شعبةِ أمراض الخديج والوليد في مشفى الأسد الجامعي باللاذقية في الفترة الواقعة بين 1/4/2007 -1/10/2008 بتشخيص متلازمة تسرّع التنفس العابر عند الوليد . وبالنظر إلى النتائج شَكّلت الذكورة والولادة القيصرية ونقص مشعر أبغار في الدقيقة الأولى أبرز عوامل الخطورة . وكان تسرّع التنفس والسحب الوربي أهم التظاهرات السريرية . وكان مظهر فرط التهوية موجوداً في معظم الصور الشعاعية للصدر . كما سجلت النتائج المخبرية انخفاضاً طفيفاً في قيم (PH) الدم الشرياني للمرضى . أما العلاج فقد أدى استخدام الفورسيمايد الوريدي إلى تخفيض فترة الاستشفاء نسبياً . Transient tachypnea of the newborn is a common disease in newborns throughout the world, justifying the increasing concern about this syndrome. Our study involved (83 newborns) with the diagnosis of transient tachypnea, who had been admitted to the Department of Neonatal – perinatal care at Al ASSAD UNIVERSITY HOSPITAL between 1/4/2007 and 1/10/2008. Results showed that the masculine gender, cesarean section, and low Apgar score at minute 1 were the major risk factors for (TTN), and the tachypnea and retractions were the major clinical findings while the hyperinflation appears in almost all the chest X-rays . The laboratory findings showed a little decrease in the PH values of blood gases. It also showed that treatment with intravenous furosemide relatively decreased the hospitalization period.